Effectiveness of a topical local anaesthetic spray as analgesia for dressing changes: A double-blinded randomised pilot trial comparing an emulsion with an aqueous lidocaine formulation - Desai, Chirag; Wood, F.; Schug, S.; Parsons, Richard; Fridlender, C.; Sunderland, Vivian Bruce (Pergamon, 2014)
Background: Partial thickness skin graft wounds are painful. Topically applied lidocaine has been used for analgesia in several clinical trials. This study compared the effectiveness of two different formulations of topical local anaesthetic for dressing changes of partial thickness skin graft donor sites.Methods: A double-blind randomised controlled, pilot trial was conducted in 29 patients undergoing split thickness skin graft surgery. Subjects were randomised to either a 3% lidocaine emulsion formulation ‘‘Treatment E’’ (NOPAYNETM) or a 4% aqueous solution ‘‘Treatment A’’ (XylocaineTM). Subjects received one spray per 3 cm2 of donor site area followed by up to two further spays as required. Endpoints included pain intensity measured by the numerical rating scale (NRS) up to 1 h after dressing change commencement, sting sensation, overall satisfaction and lidocaine plasma concentration.Results: The 60 min pain scores for E and A were 1.3 ±0.3 (mean ±SEM) and 1.8 ±0.4 (ƿ = 0.98) respectively. Nearly 90% of patients were very satisfied with their treatment. The mean plasma concentrations of lidocaine for A and E were 0.132 mg/l and 0.040 mg/l respectively (ƿ = 0.069).Conclusion: The topical local anaesthetic formulations achieved low pain scores during dressing changes. The safety profile was potentially improved with the emulsion formulation of lidocaine.